Impacts of dynamic capillary pressure effects in supercritical CO2-Water flow: Experiments and numerical simulations. (February 2020) - Abidoye, Luqman K.; Das, Diganta B.
Highlights: Controlled laboratory scale experiments done for supercritical CO2- water flow. High-pressure and high-temperature experimental rig used. Capillary pressure–saturation relationships determined for supercritical CO2- water flow. Numerical simulations of the dynamic capillary pressure effect carried out. Dynamic capillary pressure effect is found to significant in the supercritical CO2- water flow. Abstract: Contrary to report that dynamic capillary pressure effect was insignificant in the supercritical CO2- water (scCO2 -water) flow system, this work found the effect to be considerable in the displacement of water or brine by injected scCO2 in the geological carbon sequestration, especially prior to the attainment of equilibrium in the system. Series of controlled laboratory scale experimental measurements and numerical simulations of the dynamic capillary pressure effect and its magnitude (dynamic coefficient, τ) for supercritical CO2- water(scCO2 -water) system are reported in unconsolidated silica sand. Novel measurement technique has been developed to achieve this purpose, by applying the concept of two-phase flow system in the context of geological carbon sequestration. This work considers the injection of scCO2 into storage aquifer as a two-phase flow system, where the CO2 displaces the resident fluid (brine or water). Using a high-pressure and high-temperature experimental rig, capillary pressure–saturation relationships (P c -S) for this flow system and the saturation rate dependencies of the P c -S relationships (quantified by dynamic coefficient, τ), known as dynamic capillary pressure effect were determined. This τ was previously unreported for scCO2 -water system. In scCO2 -water flow system, τ ranges from 2 × 10 5 to 6 × 10 5  Pa s at high water saturation and 1.3 × 10 6 to 8 × 10 6  Pa saround the irreducible saturation. τ increases with rising temperature but decreases with increase in porous medium permeability. Numerically determined τ-S relationships compare well with the corresponding experimental results for wide range of water saturation.The implication was that water saturation of the porous media will be considerably underestimated, if the dynamic capillary pressure effect was ignored in the characterization of the scCO2-water flow system, i.e., if only equilibrium Pcrelationship was used.